x(21+x*x-10x)-26=0

Simple and best practice solution for x(21+x*x-10x)-26=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(21+x*x-10x)-26=0 equation:


Simplifying
x(21 + x * x + -10x) + -26 = 0

Multiply x * x
x(21 + x2 + -10x) + -26 = 0

Reorder the terms:
x(21 + -10x + x2) + -26 = 0
(21 * x + -10x * x + x2 * x) + -26 = 0
(21x + -10x2 + x3) + -26 = 0

Reorder the terms:
-26 + 21x + -10x2 + x3 = 0

Solving
-26 + 21x + -10x2 + x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| a^2*2=16 | | 7b(-2b)= | | 3x+5=.20(15x+10) | | (2.35+2.71i)(4.9i+3.32i)= | | 7-2y=3 | | (2.35+2.71i)-(4.9i+3.32i)= | | 75=3(-10+-3)+6 | | 1x+2y=-3 | | 3x^3+8x^2-15x+4=0 | | 4(x+1)-5=x-1+3x | | 3(2x-1)+1=10 | | 5(-3x-2)-(x-3)=4(4x+5)+13 | | 4de-de= | | (2+3i)+(2-5i)= | | 6(-5-16)=30y+84 | | 5x-3=144 | | 6.86x+4=47.0596+2x | | 9+10=21-3 | | 3(x-18)=3x+18 | | 2+6x-7=8+2x-10+4 | | 3x-7=-18 | | 6-x+4=6-x-4 | | (-3*-n)-7=n+1 | | 5x+3=144 | | V=6*6-2*6 | | ln(23)=x | | (6+2i)-(-1+2i)= | | 4m*2-8mn= | | (-3x-n)-7=n+1 | | 12ab+18b*2= | | a*2+ab-6a= | | yw+yz=r |

Equations solver categories